Mitigating Extra-Firm Risk Environments – The Case of Turkish Firms in Germany - Philip Völlers (Tijdschrift voor economische en sociale geografie, 2023)
Recent studies claim that the extra-firm environment as a causal driver for configuration processes in global production networks is understudied. The case of Turkish cross-border foreign direct investment into Germany is analysed to facilitate a better understanding of how transnationally embedded firms perceive and respond to extra-firm risk environments. The global production network lens frames the discussion, applying the analytical categories of embeddedness, risk and value. Qualitative interviews with 15 Turkish firm managers in Germany and 24 experts in the field of Turkish-German business relations were conducted. The analysis shows that transnationally embedded Turkish firms respond to extra-firm risks by deepening their territorial embeddedness in the host country. While mimicking domestic firms on the level of societal embeddedness, Turkish firms dissociate from risk narratives related to their home country and valorise their association with the German embeddedness context on the firm and network level.
Keywords: 330; global production networks; risk; embeddedness; Turkey; Germany; FDI